Gelatinous zooplankton abundance at Sylt Roads - Wadden Sea off List, Sylt, North Sea in 2021 - Timm Kress; Birgit Hussel; Petra Kadel; Ragnhild Asmus; Harald Asmus; Johannes J Rick; Karen Helen Wiltshire (PANGAEA, 2022)
In order to monitor long-term variability in or eventual change of the planktonic community a semi-quantitative analysis of gelatinous zooplankton has been ongoing since 2009 in the Sylt-Rømø Bight, a region of high ecological importance within the Marine Protected Area National Park Schleswig Holsteinisches Wattenmeer. The sampling is tightly linked to the LTER Sylt Roads time series thus enabling the coupling of species occurrence to the respective hydrochemical and physical conditions in the water column.